Development and Testing of Zeolite-Based Slow Release Fertilizer NZEO-SR in Water and Soil Media - Kharisun Kharisun; Mohammad Rif’an; Mochamad Nazarudin Budiono; Ruly Eko Kusuma Kurniawan (Faculty of Agriculture, Universitas Sebelas Maret, 2017)
The research was carried out in the Laboratory of Soil Science and greenhouse Agriculture Faculty, Jenderal Soedirman University. This experiment was aimed at studying the effects of fertilizer adhesive levels and fertilizer granule size on water penetration, water, and soil chemical properties. The research was laid out according to Completely Randomized Design (CRD), consisting of 2 factors i.e. fertilizer granule size (2 sizes) and fertilizer adhesive (5 levels). There were 10 types of NZEO-SR fertilizers tested with 3 replications. The fertilizers were tested in water and soil media, totaling 60 experimental units. The results showed that NZEO-SR fertilizer having a diameter of 2.5 - 3.0 mm in combination with 3% (w/w) fertilizer adhesive had the highest ability to resist water penetration. Levels of fertilizer adhesive material gave significant effects on pH (H2O), electrical conductivity (EC) and water-soluble N. Diameter of fertilizer had no effect on all the variables studied, except for water-soluble N. Levels of fertilizer adhesive significantly affected the pH (H2O) and total soil N, but did not show significant effects on the EC and soil available N. The diameter of fertilizer had no effect on all soil chemical variables.